Effects of Microglial Activation and Polarization on Brain Injury After Stroke - Dong, Rui; Huang, Renxuan; Wang, Jiaoqi; Liu, Hongyu; Xu, Zhongxin (Frontiers in Neurology, 2021)
Stroke is one of the most common causes of death worldwide. The subsequent development of neuroinflammation and brain edema dramatically increases the risks associated with stroke, leading to a substantial increase in mortality. Although considerable progress has been made in improving cerebral perfusion in the acute phase of stroke, effective treatment options for the subacute and chronic phases associated with cerebral infarction are limited. Microglia, the innate immune cells of the central nervous system (CNS), can be activated and polarized to take on different phenotypes in response to stimulations associated with stroke, including pro-inflammatory and anti-inflammatory phenotypes, which affect the prognosis of stroke. Therefore, investigation of the activation and polarizing mechanisms of microglia plays a critical role in treating stroke. The aim of this article was to investigate the significance of microglial phenotype regulation in stroke treatment by summarizing the activation, polarizing mechanisms, and general microglia characteristics.